Arabidopsis kinesins KCH3 and KCH7 promote root gravitropism through actin bundling in the stele - Yingzhi Niu; Shuyuan Chen; Zhaoguo Deng; Juan Du; Yangyang Zhou; Ni Fan; Dingding Zhou; Yue Niu; Yang Yang; Lizhe An; Siyi Chen; Yun Xiang; et al. (Proceedings of the National Academy of Sciences, 2025)
Root gravitropism is essential for plant adaptation to the environment. The cytoskeleton is known to play a critical role in gravitropism, but the underlying mechanisms remain unclear. In this study, we demonstrate that the Arabidopsis kinesins KCH3 and KCH7 (KCH3/7) are expressed and functionally active in the root stele. The kch3 kch7 ( kch37 ) double mutant exhibits delayed gravitropic responses, while stele-specific expression of either KCH3 or KCH7 rescues this defect. Both the calponin homology (CH) and motor domains of KCH3/7 are essential for mediating gravitropism. In vitro and in vivo assays reveal that KCH3/7 promotes actin filament (F-actin) bundling and its turnover in the root stele. Mutation of KCH3/7 results in altered PIN protein abundance and polarity in the root stele, leading to impaired acropetal auxin transport within the stele and reduced auxin accumulation in the root tip’s columella cells. This ultimately causes defective auxin redistribution during gravistimulation. Collectively, our findings highlight the importance of cytoskeletal organization and dynamics in the root stele for maintaining the auxin gradient in the root tip and for gravistimulation-induced auxin asymmetry.